2015
DOI: 10.1111/bjh.13780
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic anti-myeloma activity of the proteasome inhibitor marizomib and the IMiD®immunomodulatory drug pomalidomide

Abstract: The proteasome inhibitor bortezomib is an effective therapy for the treatment of relapsed and refractory multiple myeloma (RRMM); however, prolonged treatment can be associated with toxicity, peripheral neuropathy and drug resistance. Our earlier studies showed that the novel proteasome inhibitor marizomib is distinct from bortezomib in its chemical structure, mechanisms of action and effects on proteasomal activities, and that it can overcome bortezomib resistance. Pomalidomide, like lenalidomide, has potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 58 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…29,41,42 Specifically, we showed that pDCs are relatively resistant to novel and conventional therapies; protect tumor cells from therapy-induced cytotoxicity; promote tumor growth and survival; as well as suppress immune responses. 29,41,42 We therefore next examined the effect of RA190 on pDC-induced MM cell growth. MM.1S cells and patient pDCs were cultured either alone or together.…”
Section: Resultsmentioning
confidence: 99%
“…29,41,42 Specifically, we showed that pDCs are relatively resistant to novel and conventional therapies; protect tumor cells from therapy-induced cytotoxicity; promote tumor growth and survival; as well as suppress immune responses. 29,41,42 We therefore next examined the effect of RA190 on pDC-induced MM cell growth. MM.1S cells and patient pDCs were cultured either alone or together.…”
Section: Resultsmentioning
confidence: 99%
“…Cell cycle analysis was performed as described previously 15 . Cell viability was assessed by WST-1/CellTiter-Glo (CTG) Luminescent assays, as in prior study 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Immunoblotting was performed as previously described 15 using antibodies against USP1, USP2, USP5, USP7, USP14, Caspase-3/8/9, p21, FANCD2, FANCI, PCNA, Rad51, GAPDH (Cell Signaling, Beverly, MA, USA); ID1, ID2, ID3, ID4, Notch-1, Notch-2, Sox-4 and Sox-2 (Bethyl Laboratories, Montgomery, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was assessed by WST-1/CellTiter-Glo Luminescent assays, as previously described 22,23 . DNA synthesis was measured by 3 H-TdR uptake.…”
Section: Methodsmentioning
confidence: 99%